Missouri Mathematics Project Model Using Problem Based Learning Approach to Increase Problem-Solving Ability (Universitas Negeri Semarang, 2019)
This study aims to discover learning tools of Missouri Mathematics Project (MMP) model using valid, practical and effective Problem Based Learning (PBL) Approach in order to increase problem-solving ability. The developed tools are considered valid based on validation analysis of matrix material learning tools. The data of the study is collected through provision test and observation. The test data is processed by learning completeness test and independent sample 2 tests. MMP learning tools development produces practical learning tools supported by lesson plan implementation analysis, teacher’s response and students’ responses. The results of the study showed as follows: The development of MMP learning tools produces valid learning tools based on professional validation and test trial of problem-solving ability, effective learning tools as it meets 75% classical learning completion, the average of class problem-solving ability using MMP model is better than class with expository, development of learning tools using MMP produces practical learning tools.